Electronic Modulation between Tungsten Nitride and Cobalt Dopants for Enhanced Hydrogen Evolution Reaction at a Wide Range of pH. Issue 11 (27th April 2020) - Liu, Zhizhong; Zhang, Xuming; Song, Hao; Yang, Yixuan; Zheng, Yang; Gao, Biao; Fu, Jijiang; Chu, Paul K.; Huo, Kaifu
Abstract: Transition metal nitrides with Pt‐like chemical properties are important electrocatalysts and tungsten nitride (WN) is a good hydrodenitrogenation and hydrodesulfurization catalyst but its catalytic activity for hydrogen evolution reaction (HER) is poor because of the unfavourable d‐band electronic structure resulting in strong interactions with adsorbed hydrogen. Herein, Co doped WN nanowire arrays grown on carbon cloth are reported and the result shows that Co dopants not only act as active sites, but also increase activity of W sites by downshifting the position of d‐band centre of W sites as a result of the electron transfer from W to Co. Density‐functional theory (DFT) and density of states (DOS) calculations confirm that the enhanced HER performance is attributed to the modulation of the d‐band center of W and introduced Co dopants both consequently facilitating the HER process. The results on electronic modulation provide insights into the design of electrocatalysts with high activity. Abstract : Co doped WN nanowire arrays grown on a carbon cloth are prepared by a facile hydrothermal method and the result shows that the Co dopants can effectively downshift the position of d‐band center of W sites as a result of the electron transfer from W to Co thereby decreasing adsorption energy of H on W in Co/WN. Consequently, both of the modulated W and introduced Co dopants facilitate the HER process.